Aspects of Hospital Criminalization in Medical Malpractice Cases That Can Create a Noble Healthcare Industry - Hendri Pangestu; Tina Amelia (Journal Customary Law, 2026)
Hospital criminalization in medical malpractice cases is an increasingly relevant legal issue as hospitals transform from social institutions into socio-economic entities in the modern healthcare industry. The constitutional right to health requires the state to ensure the provision of safe, high-quality, and equitable healthcare services. However, law enforcement practices are still dominated by an individual accountability approach that leads to the criminalization of healthcare workers and ignores the role of hospital policies and service systems. This situation creates an imbalance of justice for both patients and healthcare workers and fails to encourage institutional improvement. This study aims to analyze the normative regulation of hospital criminalization as a corporation, identify the problems of its implementation, and formulate an ideal concept of criminalization that aligns with substantive justice and the social function of hospitals. The method employed is normative legal research with a statutory and conceptual approach, through a study of health law, criminal law, and the doctrine of corporate criminal liability. The results show that the regulation of hospital criminalization still contains unclear parameters of institutional error and does not fully accommodate a systemic approach. Hospital criminalization should be positioned as a corrective instrument that encourages improved governance, a culture of patient safety, and ethical healthcare practices. This allows criminal law to play a role in safeguarding the humanitarian and social function of hospitals as part of the noble healthcare industry.